How Do You Think the Victims of Bullying Feel? A Study of Moral Emotions in Primary School - Romera, Eva M.; Ortega-Ruiz, Rosario; Rodríguez-Barbero, Sacramento; Falla, Daniel (Frontiers in Psychology, 2019)
The important role of morality in the transgressive behaviour which occurs within peer groups, such as bullying, has often been observed. However, little attention has been paid to this kind of violence in the initial stages of primary education. This study aims to analyse the attribution of moral emotions (self and other) to victims in different bullying types (verbal, physical, relational and exclusion) and roles (aggressor and victim). An ad hoc questionnaire with supporting stick–figure cartoons was used. In total, 1150 schoolchildren between the ages of 6 and 11 took part in the study (50.3% girls). The results showed that over 80% of schoolchildren had been involved in any type of aggressive behaviour, and that there were significant differences by gender, year and involvement in self- and other-attributed moral emotions. Aggressors showed less shame in general. In self-attribution situations, there was a greater indifference in aggressors. Victims had less shame and greater indifference in self-attributions for verbal and physical aggression. Girls recognized higher percentages of guilt in victims. The main moral emotion in the first stage was shame. This tendency changed to guilt as the children got older in both situations. Results support the need for the study of moral emotions development of victims and aggressors. How the experience of being involved in bullying biases the moral interpretation towards from the feelings of the victim is discussed.